Exploring the drivers of price variation in orthopaedic radical bone tumor resection: A nationwide database study - Devika A. Shenoy; William C. Cruz; Shamik Bhat; Katelyn Parsons; Aaron D. Therien; Kevin A. Wu; Christian A. Pean; William C. Eward (PLoS ONE, 2026)
Background Radical resection of bone tumors is a clinically effective but costly procedure. Despite the implementation of federal price transparency mandates, little is known about the nationwide variation in negotiated prices for these specialized oncologic surgeries. This study aimed to quantify the variation in negotiated rates for radical resection of the humerus and femur/knee and identify associated hospital, payor, and state-policy drivers. Methods This cross-sectional study analyzed hospital-negotiated payor rates from the Turquoise Health database for current procedural terminology (CPT) codes 24150 (humerus resection) and 27365 (femur/knee resection). Multivariate linear regression was used to determine the associations between hospital size and type, payor class, and state-level policies (Medicaid expansion, Certificate of Need [CoN] laws, All-Payer Claims Database [APCD] mandates, and Nurse Practitioner [NP] scope of practice) on negotiated payor rates. Results A total of 285,857 negotiated rates were analyzed. Significant price variation was observed across all factors. Large hospitals (>1000 beds) and Critical Access Hospitals (for femur/knee resection only) had significantly higher rates. CoN laws were associated with higher prices for both procedures (+$348.25 and +$667.98, respectively), as were APCD mandates for femur/knee resections (+$1231.24). Medicare Advantage plans paid inconsistently compared to commercial plans, paying more for humerus but substantially less for femur/knee resections. Discussion Negotiated prices for radical bone tumor resection are highly variable and influenced by a complex interplay of market dynamics, challenging the assumption that price transparency alone can standardize healthcare costs for specialized care.